Graves’ disease – management of Graves’ orbitopathy and thyrotoxicosis, including new therapies - Agata Toboła; Małgorzata Gietka-Czernel (Wiedza Medyczna, 2023)
Graves' disease (GD) is the most common cause of hyperthyroidism in countries with adequate iodine supply, and its main extrathyroid manifestation is thyroid orbitopathy. For many years, thyrotoxicosis has been treated with antithyroid drugs, radioactive iodine therapy and thyroidectomy, and glucocorticoids have remained the standard treatment of thyroid eye disease (TED). Currently, there is a growing trend of using targeted therapies in the treatment of thyroid orbitopathy (TO). The significant development of immunobiology, a better understanding of the pathophysiology of the disease and a multitude of studies on new therapies give hope for better treatment results and an improvement in the quality of life of patients.The aim of the paper is to discuss the current principles of management of Graves' disease, including thyroid orbitopathy, with particular emphasis on new therapeutic methods. The potent role of K1-70TM and small molecule thyroid stimulating hormone (TSH) receptor antagonists in the treatment of hyperthyroidism is indicated. Not only do we point out the promising outcomes of combining glucocorticoids with mycophenolates, but also highlight the use of teprotumumab, rituximab, cyclosporin A, azathioprine, methotrexate, tocilizumab and sirolimus in the therapy of active moderate to severe form of orbitopathy. The protective and supportive effect of statins in the treatment of TED is noted. The limitations of the research results mentioned in the paper are remarked and the need for further randomized studies of long-term safety and efficacy in a larger group of patients is underlined.